Analisis Pengaruh Iklan dan Brand Ambassador Terhadap Keputusan Pembelian Produk Busana Muslim Nibras - Neni Wahyuni; Husnayetti Husnayetti (Indonesian Journal of Economics Application (IJEA), 2020)
In the current era of globalization has resulted in business competition more dynamic, complex, and there are many challenges faced by companies. Various forms of marketing strategies must be carried out by companies to compete with competitors and new entrants who are increasingly emerging. Companies are competing to attract potential consumers through advertising media that are currently popular. Besides, to select the right advertising media, companies must also look for supporting media for the advertisement such as using an attractive Brand Ambassador. The research objective is to analyze how the influence of advertising and Brand Ambassador on purchasing decision for Muslim clothing product at PT Fatahillah Anugerah Nibras. The research design uses the quantitive descriptive associative method in determining the relationship between the independent variables consisting of advertisement with the dimensions of Instagram, Youtube, Facebook, Website and Brand Ambassador with dimensions of visibility, credibility, attraction, power and the dependent variable is the product purchase decision. The sample in this research has reached 100 respondents using purposive sampling technique where the sample was determined with certain considerations or criteria so it could support this research. Data collection Instrument used an online questionnaire. The data analysis tool used is SEM (Structural Equation Modeling) with Smart PLS 3.0. The research result shows that advertising has a positive and significant effect on purchasing decisions, and Brand Ambassador has a positive and significant impact on purchasing decisions. The exogenous variables (advertising and brand ambassador) and their dimensions are carried out intensely simultaneously. It will have a positive effect on improving purchasing decisions.